PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MENGGUNAKAN MODEL DISCOVERY LEARNING PADA POKOK BAHASAN IDENTITAS TRIGONOMETRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI MIPA 3 SMA NEGERI PAKUSARI TAHUN PELAJARAN 2019/2020 - Komariyah Komariyah (saintifika, 2020)
This research is based on the following problems: (a) How to increase student achievement by implementing the cooperative learning method of the Discovery Learning model in class XI MIPA 3 students of SMA Negeri Pakusari, Jember Regency, 2019/2020 Academic Year ". (b) How does the cooperative learning method of the Discovery Learning model affect the learning motivation of class XI MIPA 3 SMA Negeri Pakusari, Jember Regency for the 2019/2020 academic year.. This study used two rounds of action research. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is 32 students of class XI MIPA 3 Pakusari State Senior High School. The data obtained were in the form of final test results, observation sheets for teaching and learning activities. From the analysis, it was found that the student's learning achievement had increased from cycle I to cycle II, namely, cycle I was 62.50% and cycle II was 94%.